2004
DOI: 10.1007/s00213-003-1744-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reinforcer type and route of administration on gamma-hydroxybutyrate discrimination in rats

Abstract: These results demonstrate that methodological variables during drug discrimination training can certainly influence the results of stimulus generalization. Future investigations into the behavioral and/or physiological mechanisms that account for these effects are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 20 publications
(41 reference statements)
5
26
0
Order By: Relevance
“…Even if the same general procedure is used, the manner in which training and testing are arranged and the techniques used to quantify performance may powerfully affect results. For example, we have demonstrated that using food versus water as reinforcers did not significantly affect the development of a vehicle-GHB discrimination in rats but did significantly affect the results of subsequent generalization tests (Baker, Pynnonen, & Poling, 2004). As another example, we have also shown that whether 50% or 100% keylight-food pairings produced "stronger" autoshaped responding in pigeons depended on whether response rate or choice was used to index performance (Picker and Poling, 1982).…”
Section: Discussionmentioning
confidence: 92%
“…Even if the same general procedure is used, the manner in which training and testing are arranged and the techniques used to quantify performance may powerfully affect results. For example, we have demonstrated that using food versus water as reinforcers did not significantly affect the development of a vehicle-GHB discrimination in rats but did significantly affect the results of subsequent generalization tests (Baker, Pynnonen, & Poling, 2004). As another example, we have also shown that whether 50% or 100% keylight-food pairings produced "stronger" autoshaped responding in pigeons depended on whether response rate or choice was used to index performance (Picker and Poling, 1982).…”
Section: Discussionmentioning
confidence: 92%
“…Increasing evidence (e.g., cross-substitution between GHB and baclofen) in rats and pigeons suggests that GABAergic activity is a major component of the discriminative stimulus effects of GHB (Colombo et al, 1998;Lobina et al, 1999;Carter et al, 2003Carter et al, , 2004aBaker et al, 2004;Koek et al, 2004). Thus, compounds that do not bind to GABA receptors might not be expected to produce or attenuate GHB-like discriminative stimulus effects, which is consistent with the relatively small amount of GHB-appropriate responding observed after administration of selective GHB receptor ligands current study) and the failure of UMB86, UMB72, or 3-HPA to fully antagonize the discriminative stimulus effects of the training dose in either rats or pigeons.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a representative compound from each chemical approach was examined in drug discrimination experiments. Drug discrimination data in rats have shown that GHB precursors and compounds that act at GABA B receptors occasion substantial GHB-appropriate responding, whereas pharmacologically unrelated compounds do not (Winter, 1981;Carter et al, 2003;Baker et al, 2004). Compounds were also examined in pigeons discriminating GHB because recent studies suggest that the discriminative stimulus effects of GHB in this species involve not only GABA B receptors, but also GABA A receptors .…”
mentioning
confidence: 99%
“…This procedure paired the sound of pellet drop with food availability, which was not contingent on any response. After this procedure, eight lever-press training sessions were conducted whereby all subjects were exposed to errorless training conditions (e.g., Baker et al 2004). Under these conditions, only one of two levers was present, depending on whether drug or vehicle was administered.…”
Section: Discrimination Training and Reinforcement Schedulesmentioning
confidence: 99%
“…In the FR schedule, a fixed number of responses by a subject on the condition-appropriate lever are reinforced. A common variation of the FR schedule includes a resetting component that punishes lever switching behavior, whereby a fixed consecutive number of responses on one lever is required for reinforcement (e.g., Baker et al 2004;Stolerman 1989b). The VI schedule, however, is dependent on the first response made after the passage of a variable interval of time.…”
Section: Introductionmentioning
confidence: 99%